Potential of the cannabinoid CB(2) receptor as a pharmacological target against inflammation in Parkinson's disease - Gómez-Gálvez, Yolanda; Palomo-Garo, Cristina; Fernández-Ruiz, Javier; García, Concepción (Progress in neuro-psychopharmacology & biological psychiatry, 2016)
Inflammation is an important pathogenic factor in Parkinson's disease (PD), so that it can contribute to kill dopaminergic neurons of the substantia nigra and to enhance the dopaminergic denervation of the striatum. The cannabinoid type-2 (CB2) receptor has been investigated as a potential anti-inflammatory and neuroprotective target in different neurodegenerative disorders, but still limited evidence has been collected in PD. Here, we show for the first time that CB2 receptors are elevated in microglial cells recruited and activated at lesioned sites in the substantia nigra of PD patients compared to control subjects. Parkinsonian inflammation can be reproduced experimentally in rodents by intrastriatal injections of lipopolysaccharide (LPS) which, through an intense activation of glial elements and peripheral infiltration, provokes a rapid deterioration of the striatum that may extend to the substantia nigra too. Using this experimental model, we recently described a much more intense deterioration of tyrosine hydroxylase (TH)-containing nigral neurons in CB2 receptor-deficient mice compared to wild-type animals, supporting a potential neuroprotective role for this receptor. In the present study, we further explored this issue. First, we found elevated levels of the CB2 receptor measured by qRT-PCR in the striatum and substantia nigra of LPS-lesioned mice, as well as an increase in the immunostaining for this receptor in the LPS-lesioned striatum. Second, we found a significant increase in CD68 immunostaining, which serve to identify activated microglia and also infiltrated peripheral macrophages, in these brain structures in response to LPS insult, which was much more intense in CB2 receptor-deficient mice in the case of the substantia nigra. Next, we observed that the activation of CB2 receptors with a selective agonist (HU-308) reversed LPS-induced elevation of CD68 immunostaining in the striatum and the parallel reduction in TH immunostaining. Lastly, we found that LPS elevated the gene expression of different pro-inflammatory mediators in both the striatum and the substantia nigra, whereas the selective activation of CB2 receptors reduced a part of these mediators, e.g. inducible nitric oxide synthase, although exclusively in the striatum. In conclusion, we have provided the first evidence on the up-regulation of CB2 receptors in glial elements in postmortem tissues of PD patients, which has been confirmed in an inflammatory model of this disease. In addition, we have provided evidence on the benefits derived from their activation in relation with the activation of microglial cells, the infiltration of macrophages and also certain capability of these cells to generate proinflammatory factors.